FIRMS’ CHARACTERISTICS: A PRELIMINARY STUDY OF FAMILY TAKAFUL DEMAND IN MALAYSIA - Romzie Rosman; Norizan Remli; Muhamad Muda (International Journal of Accounting, Finance and Business, 2018)
This paper aims to examine the impact of firms’ characteristics namely income, age, size and agents on Family Takaful demand in Malaysia. Secondary data are used to conduct the hypotheses testing on 25 Takaful operators which offer Family Takaful protection in Malaysia from the year 2008-2016. The regression model pooled OLS, randomeffect model and fixed-effect model were conducted. The Hausman test results showed that the random-effect model is better than the fixed-effect model. The results showed that the size of the firms (lSize) and agents’ performance (lFees) were positive and they significantly affected family Takaful demand in Malaysia. Firms’ income (lInc) and firms’ age (Age) were negative and insignificant in explaining the Family Takaful demand in Malaysia. Hence, these findings suggest that the size of the business and promoting a good agents’ performance within firms is important in order to uphold the industry sustainability.